PENGARUH RISIKO PEMBIAYAAN DAN RISIKO LIKUIDITAS TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2018-2020 (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2023)
This study aims to examine the effect of financing risk and liquidity risk on the profitability of Islamic commercial banks for the 2018-2020 period. The sampling technique used is purposive sampling. The sample used is a Sharia Commercial Bank registered with the Financial Services Authority (OJK). Based on the purposive sampling method, 11 Islamic Commercial Banks meet the criteria. The results of this study indicate that partial liquidity risk does not affect the profitability of Islamic commercial banks. In contrast, financing risk influences the profitability of Islamic commercial banks. This study also shows that financing and liquidity risks simultaneously affect Islamic commercial banks' profitability. Based on the calculations carried out in this study, the results showed that the financing risk level could affect Islamic commercial banks' profitability.